Wage effects of labor market tightness - Christian Philip Hoeck (Danmarks Nationalbank, 2022)
I provide new microeconometric estimates of the effect of labor market tightness on wages at the firm level. Using Danish data on vacancies and unemployment at the occupational level and firm data on the occupational composition of employees, I construct firm-specific measures of labor market tightness. Using this measure, I find an elasticity of wages with respect to tightness of 0.01-0.02, which implies an increasing but relatively flat wage-setting curve. The results are in line with the qualitative implications of the canonical search-andmatching model of the labor market.
Keywords: E24; J31; J63; 330; Inflation; wages and prices; economic activity and employment